Bone growth, limb proportions and non-specific stress in archaeological populations from Croatia. (March 2014) - Pinhasi, R.; Timpson, A.; Thomas, M.; Šlaus, M.
Abstract Background: The effect of environmental factors and, in particular, non-specific stress on the growth patterns of limbs and other body dimensions of children from past populations is not well understood. Aims: This study assesses whether growth of mediaeval and post-mediaeval children aged between 0–11.5 years from Adriatic (coastal) and continental Croatia varies by region and by the prevalence and type of non-specific stress. Methods: Dental ages were estimated using the Moorrees, Fanning and Hunt (MFH) scoring method. Growth of long bone diaphyses (femur, tibia, humerus, radius and ulna) was assessed by using a composite Z-score statistic (CZS). Clavicular length was measured as a proxy for upper trunk width, distal metaphyseal width of the femur was measured as a proxy for body mass and upper and lower intra-limb indices were calculated. Differences between sub-sets sampled by (a) region and (b) active vs healed non-specific stress indicators and (c) intra-limb indices were tested by Mann–Whitney U-tests and Analysis of Covariance (ANCOVA). Results: Adriatic children attained larger dimensions-per-age than continental children. Children with healed stress lesions had larger dimensions-per-age than those with active lesions. No inter-regional difference was found in intra-limb indices. Conclusion: These findings highlight the complexity of growth patterns in past populations and indicate that variation in environmental conditions such as diet and differences in the nature of non-specific stress lesions both exert a significant effect on long bone growth.